Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
CHI '10 Extended Abstracts on Human Factors in Computing Systems 2010
DOI: 10.1145/1753846.1754135
|View full text |Cite
|
Sign up to set email alerts
|

The effect of eco-driving system towards sustainable driving behavior

Abstract: In this paper, we explore the use of an Eco-Driving System [1] to see how the system promotes greener driving behavior. We conducted both an online survey (N=60) and a user test (N=14) to study the EcoDriving System. Based on participant responses, we found that the current Eco-Driving System shows minor benefits in gas mileage due to different driving behaviors and also increased task loads for our participants. Therefore, we suggest a new research direction for the Eco-Driving System for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 4 publications
4
12
0
Order By: Relevance
“…Figure 10 below shows the ranking of the six reward types that participants were presented with. This result is aligned with published research by Lee et al [11] which shows that money is an important reason for which people would like to improve their fuel efficiency.…”
Section: P38supporting
confidence: 91%
“…Figure 10 below shows the ranking of the six reward types that participants were presented with. This result is aligned with published research by Lee et al [11] which shows that money is an important reason for which people would like to improve their fuel efficiency.…”
Section: P38supporting
confidence: 91%
“…Considering the definition of sustainability and the topic of traffic expression, the use of computational methods to monitor and assess and optimize the transport efficiency are already used in systems today [2], [13], [14]. Nevertheless, the efficiency problem need to consider all dimensions of sustainability in order to become complete.…”
Section: A Computational Problemmentioning
confidence: 99%
“…Reference [12] highlighted that inflated risk levels can be induced by distraction through inappropriate feedback. This was further illustrated by [10] who found that drivers, as a result of amplified cognitive workload and stress levels, ignored feedback provided by a non-user-friendly design or a poorly positioned system on their dashboard during a field test. However, real-time and context related feedback is integral when promoting fuel efficiency of individuals during driving.…”
Section: Appltca Nonmentioning
confidence: 99%
“…However, other studies in this research domain have involved even smaller sample sizes (n < 20) [4], or the treatment period was shorter [10] or based on a driving simulator [9] [1 0]. Findings which entail a lager sample size were mainly conducted with truck drivers and did not evaluate an eco-driving smartphone application with different feedback meters in combination with ODP, rather a fixed installed on board system that constantly monitored the driving behavior.…”
Section: Viti Limitations and Future Researchmentioning
confidence: 99%